2013
DOI: 10.1007/s12665-012-2213-y
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogam covers on sepulchral monuments and re-colonization of a marble surface after cleaning

Abstract: Re-colonization of freshly cleaned surfaces by aeroterrestrial microbial communities is up to now poorly understood. Here, we present a comparative study addressing the composition of algal and fungal communities on a marble sculpture, based upon the analysis of 18S rRNA gene clone libraries from environmental samples. The samples were taken from a blackish and greenish biofilm cover before surface cleaning and 1 year after cleaning treatment, when traces of re-colonization became visible to the naked eye. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…An uncultured Exophiala sp. with 98 % identity to the ex-type strain of E. aquamarina (CBS 119918) in the 18S rDNA gene was reported as one of the main fungi colonizing a marble monument in Germany (Hallmann et al 2013). In that study, the fungus was identified as E. aquamarina but, taking into account its terrestrial habitat and that 18S is a relatively conserved gene (Iwen et al 2002), almost certainly the fungus on marble represents a different but related taxon.…”
Section: Discussionmentioning
confidence: 90%
“…An uncultured Exophiala sp. with 98 % identity to the ex-type strain of E. aquamarina (CBS 119918) in the 18S rDNA gene was reported as one of the main fungi colonizing a marble monument in Germany (Hallmann et al 2013). In that study, the fungus was identified as E. aquamarina but, taking into account its terrestrial habitat and that 18S is a relatively conserved gene (Iwen et al 2002), almost certainly the fungus on marble represents a different but related taxon.…”
Section: Discussionmentioning
confidence: 90%
“…Sarcinomyces are black meristematic yeasts capable of producing pigments such as melanin [43] and may cause irreversible damage to stone sculptures [44]. Since many black fungi are pleomorphic and have anamorphic life cycles with widely divergent types of propagation, morphology offers only a presumptive identification at the genus level [16].…”
Section: Effect Of Environmental Factors On Rock-inhabiting Fungal Comentioning
confidence: 99%
“…Moreover, there are species that can produce melanin, such as Capnobotryella sp. and Sarcinomyces sp., which may compromise the surface of the stones from the aesthetic and structural perspective [43]. Thus, the vast majority of species can also present a lichen association and be susceptible to air pollution, such as Physcia aipolia [49].…”
Section: Effect Of Environmental Factors On Rock-inhabiting Fungal Comentioning
confidence: 99%
“…The use of stone in the construction of monuments and sculptures has had some consequences over time, like the appearance of patinas [8] such as black films or biofilms [9]. These patinas have been identified in granite substrates [10][11][12], marble [13], all over the world, like Italian stone monuments [14] and historical monuments in Brazil [15][16][17].…”
Section: Biocidal Effect Of Gamma Radiation On the Ecology Of Filamenmentioning
confidence: 99%